PENGUATAN MODERASI BERAGAMA PADA SANTRI TPA MELALUI LITERASI KEAGAMAAN DI DESA GANTAR, INDRAMAYU - Amalia Khoerani; Aufa Zakiya Faizza; Annada Fatiha Yahya; Supriadi Maud (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Instilling the values of tolerance from an early age is a strategic effort to strengthen religious moderation and religious literacy within a pluralistic society. This community service program aimed to enhance students' understanding of tolerance as an implementation of Islam rahmatan lil 'alamin through learning activities based on storytelling and role playing. The program was conducted at Al-Mujahidin Mosque Qur'anic Learning Center (TPA) in Gantar Village, Indramayu Regency using a participatory approach consisting of four stages: preparation, educational sessions, practical activities, and evaluation and reflection. Evaluation was carried out through observations of students' participation, engagement during learning activities, and their ability to explain the values of tolerance after the program. The results demonstrated that experiential and communicative learning successfully increased students' participation, strengthened their understanding of mutual respect, and encouraged the implementation of tolerant attitudes in daily life. The success of the program was further supported by dialogic interpersonal communication between facilitators and participants, enabling a more effective internalization of Islamic values. This program indicates that integrating storytelling and role playing can serve as an alternative learning approach to strengthening religious moderation, improving religious literacy, and fostering tolerant religious character among children from an early age.